2018
DOI: 10.1039/c8ra02260g
|View full text |Cite
|
Sign up to set email alerts
|

Raman photostability of off-resonant gap-enhanced Raman tags

Abstract: Off-resonant gap-enhanced Raman tags (GERTs) show ultrahigh Raman enhancement and photostabilities and therefore can be used as ideal highly photostable nanoprobes for high-speed and high-resolution Raman bioimaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Embedding internal standards inside the core–shell nanoparticles (NPs) is a smarter approach than immobilizing them on the surface of NPs since it can avoid desorption of reporter molecules from the surface and disturbance from the biological environment or additional NP aggregation‐induced electromagnetic hot spots. We have previously reported the successful synthesis of Au–Au core–shell gap‐enhanced Raman tags (GERTs) with 1,4‐benzenedithiol (1,4‐BDT) molecules embedded, which are advantageous SERS nanoprobes with internal standards. For this high sensitivity quantitative biosensing application, we instead take advantage of the superior plasmonic enhancement of Ag and fabricate Au–Ag core–shell NPs with Raman reporters embedded as the SERS nanoprobes for improved signal to noise ratios and greater detection sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embedding internal standards inside the core–shell nanoparticles (NPs) is a smarter approach than immobilizing them on the surface of NPs since it can avoid desorption of reporter molecules from the surface and disturbance from the biological environment or additional NP aggregation‐induced electromagnetic hot spots. We have previously reported the successful synthesis of Au–Au core–shell gap‐enhanced Raman tags (GERTs) with 1,4‐benzenedithiol (1,4‐BDT) molecules embedded, which are advantageous SERS nanoprobes with internal standards. For this high sensitivity quantitative biosensing application, we instead take advantage of the superior plasmonic enhancement of Ag and fabricate Au–Ag core–shell NPs with Raman reporters embedded as the SERS nanoprobes for improved signal to noise ratios and greater detection sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Embedding internal standards inside the core-shell nanoparticles (NPs) [30][31][32][33][34] is a smarter approach than immobilizing them on the surface of NPs [29,[35][36][37] since it can avoid desorption of reporter molecules from the surface and disturbance from the biological environment or additional NP aggregation-induced electromagnetic hot spots. We have previously reported the successful synthesis of Au-Au core-shell gap-enhanced Raman tags (GERTs) with 1,4-benzenedithiol (1,4-BDT) molecules embedded, [38][39][40][41][42][43][44][45] which are advantageous SERS nanoprobes with internal standards. For this high sensitivity quantitative biosensing application, we instead take advantage of the superior plasmonic enhancement of Ag [46] and fabricate Au-Ag core-shell NPs with Raman reporters embedded as the SERS nanoprobes for improved signal to noise ratios and greater detection sensitivity.In the system of SERS quantitative analysis with internal standards, there are multiple signals from different components Cholesterol is an essential molecule for many processes in the human body and many diseases such as hypertension, coronary heart disease, atherosclerosis, and lipid metabolism dysfunction can be detected in their early stages by monitoring intracellular cholesterol levels.…”
mentioning
confidence: 99%
“…The rate constant may also be increased due to photothermal effects in the vicinity of the nanoparticle surfaces, because aggregated nanoparticles demonstrate absorption at the excitation wavelength (785 nm). 36,37 As a result of the interplay between these factors, the SERS intensity increased for all major peaks in the crystal violet spectrum (Fig. 6).…”
Section: Resultsmentioning
confidence: 96%
“…2d) and the narrow linewidths of their vibrational Raman bands (see detailed mode assignments in Supplementary Table 1) along with their unique spectral profiles allows use of demultiplexing methods (e.g., CLS) to obtain a large encoding capacity. The off-resonantly excited GERTs (with a localized surface plasmon resonance in the visible range but excited by 785 nm near-infrared laser) show large Raman enhancement due to a combination of electromagnetic field enhancement and electron transport effect across molecular layer in the nanogaps 41,48 , and therefore lead to a number of important properties favorable for PUF labels: (1) large enhancement factor, detectable down to a single-NP level 42,49 , leading to the fastest (to the best of our knowledge) readout speed with a good signal-to-noise ratio; (2) ultra-photostability under repeated readout due to the offresonance excitation condition 37,50,51 , leading to excellent reproducibility; (3) ultra-stable material properties in various environments (for example, humid environment), resulting in easy storage and a long shelf-life of prepared labels 37 ; (4) suitability for NIR laser excitation, resulting in low Raman background from the PUF substrate or package materials. We have to emphasize that the conventional plasmonic dimers or aggregates are inappropriate for the PUF labels since the SERS hot spots from them are apt to photobleaching 37,52 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, instability of the laser power, variation of the photon detection efficiency of the charge-coupled device (CCD) induced by temperature variation, and shift in optical alignment 55 can exert pronounced negative effects on the reproducibility of PUF labels. In addition, our previous work has shown that the Raman signals of GERTs may fluctuate under continuous laser irradiation, probably induced by the reorientation and decomposition of Raman reporter molecules 50 . Table S2 shows that I 11′ for binary encoding is larger than that for quaternary encoding, which makes sense since the former has only two responses per pixel, half of the latter.…”
Section: Resultsmentioning
confidence: 99%